REVISITING ASIAN VALUES IN SOUTHEAST ASIAN’S CYBERDEMOCRACY DISCOURSE - Juned, Mansur (Universitas Padjadjaran, 2023)
The question of democracy and cyberdemocracy within the expanding population of internet users in Southeast Asia is a prevalent and debatable concern in the region. The phenomenon is perceived as sign of better democratization while also concerned for its political destabilization effects. Recent instances of cyber sovereignty, cybersecurity, and cyberdemocracy in contrasting practical applications indicate the imperative need for an alternate paradigm to comprehend the underlying issue comprehensively. This study employs a regionalism framework to comprehensively understand the issue by investigating overarching indicators of cyberdemocracy and cases of cyberdemocracy in Southeast Asian countries through case study in qualitative method framework. this article uses library research and limited content analysis of academic literature, regional agreements, and material from news media as data sources. Limited content analysis and data triangulation are used to ensure data validity and to acknowledge the data sources’ bias before the findings are analyzed and concluded. The results indicate that Asian values significantly influence the configuration of cyber sovereignty, which integrates the Chinese concept of regulated cyber sovereignty with the Western notion of freedom in the digital realm, resulting in a cyberdemocracy driven by state governments in the region. The research findings also indicate that this state is influenced by preexisting Asian values and the region’s prevalent challenge of digital transformation.